Anticandidal Efficacy of Erythrosine with Nano-TiO2 and Blue LED-Mediated Photodynamic Therapy against Candida albicans Biofilms on Acrylic Resin: A Preliminary Study - Damrongrungruang, Teerasak; Puasiri, Subin; Vongtavatchai, Vichakorn; Saeng-on, Chatchai; Petcharapiruch, Teeruch; Teerakapong, Aroon; Sangpanya, Angkhana (European Journal of Dentistry, 2023)
Objective Incorporating an enhancer such as nano-titanium dioxide into antimicrobial photodynamic therapy can improve treatment outcome.This study aimed to compare the anticandidal efficacy of photodynamic therapy by erythrosine with nano-titanium dioxide (nano-TiO2) stimulated by a blue light emitting diode with three standard dental antifungal agents.Materials and Methods Candida albicans biofilms on acrylic resin plates were treated for 15 minutes with either nystatin, fluconazole, Polident, 220µM erythrosine + 1% (w/w) nano-TiO2 + 15 J/cm2 blue light photodynamic therapy (Ery PDT), or distilled water. For the Ery PDT group, blue light was applied for 1 minute after incubation. After 1, 3, and 6 hours, the colony forming units in log10 (log10CFU/mL) were compared. The ultrastructure of C. albicans on the acrylic resin plates treated with erythrosine + nano-TiO2 + blue light was examined using transmission electron microscopy at magnification of 30,000x.Results After 1 hour, nystatin, Polident, and Ery PDT indifferently inhibited C. albicans. At 6 hours, Ery PDT reduced the number of viable C. albicans in biofilms by 0.28log10 CFU/mL, which was equal to the effect of fluconazole and Polident. Transmission electron microscopy demonstrated that Ery PDT altered the C. albicans cell morphology by inducing cell wall/membrane rupture.Conclusion Photodynamic therapy with erythrosine + nano-TiO2 + blue light at low light power density (15 J/cm2) was as effective at inhibiting C. albicans biofilm on acrylic resin as fluconazole and Polident.
Keywords: C. albicans; erythrosine; light emitting diode; nano-titanium dioxide; nystatin; photodynamic therapy